A magyar oktatástörténet szociológiai narratívája: In memoriam Pierre Bourdieu - NagyPéter Tibor (Szociológiai Szemle, 2024)
This study provides an overview of the history of the educational policy in Hungary between 1867-1949. The following main periods of the education policy can be distinguished: During the period from 1765 to 1867, which is the period of the authoritatively dictated, not-constitutional modernism, there was no relevant co-operation between the sovereign and the civil actors of the educational field. 1.) THE PERIOD OF THE CONSTITUTIONAL EDUCATIONAL POLICY (1867-1920) From 1867 to 1876 the government aimed to rule and to modernize the education without any relevant co-operation with the local aristocracy. From 1867 to 1890 there has been a balance of power established among the local aristocracy, the church — which was the major contributor to the maintenance of schools — and the VKM (Ministry of Religion and Educational Matters). Form 1890 to 1920 there were new players who joined this equilibrium: the industrial and commercial educational societies, the movements of the teacher and schoolmaster and the growing contribution of the State to the maintenance of schools, mainly in respect of the state-schools of the various minorities and the trade schools. Nevertheless, the growing influence of the state was always balanced with another pole, e.g. by the participation of the judiciary. 2.) THE PERIOD OF THE TRANSIT10N (1920-1934) The erisis of the equilibrium policy has started after 1919. The main characteristic of this policy is that the balance between the different influences - on one side the secular educational policy of the state and on the other side the influence of the church as financial supporter of the schools - was followed by their cooperation under the guide of the ideology o f the Christian Nationalism whereby the situation of the free competition and “equal” opportunities in the education has been replaced by restrictions on origin (numerus clausus). 3.) THE PERIOD OF THE EXPANSION OF THE STATE (From 1934) The state aimed to strengthen its influence on regulating the types of the schools and their control. The system of the different types of schools (elementary school, trade school, high school) became inflexible and this restriction contributed to the division of the society into different classes and to the ideological pressure on the everyday life. The political vocation of the school inspectorate and the intensity of the control are similar to those typical in a totalitarian society. In a society where there is no respect for the result-oriented professionalism in the commerce and in the everyday life, the education remains authoritarian and ideological, because the goal of such “general” education is not to allow the formation of a modem civilized society. Where the upperclass is able to force the vanish of the achievements of the professionalism developed during several decades and in a situation where the ones with better qualities are given worse educational opportunities, it is obvious that building a carrier does not require professionalism, but symbolical knowledge, or not even knowledge, but only a well-established connection to the required upperclass.